Quality assurance policies and implementation in nursing and midwifery training colleges in Ghana - Philip Anyelba Tankpara; Dickson Adom; Joe Adu-Agyem (Institute of Advanced Engineering and Science, 2021)
The study assessed internal quality assurance (QA) systems in health training institutions in the Upper West Region. The study adopted the cross-section analytical design with a sample size of 272 (67 health tutors and 205 final year nursing students) using systematic and purposive sampling techniques. Data for the study were collected with a questionnaire and analyzed using SPSS and Stata. The study revealed that the majority (5 of 7) of nursing and midwifery colleges (NMTCs) in the Upper West Region have no quality assurance policy available, 65.7% of tutors indicated their institutions had quality assurance units/committees however these committees are inactive the total level of QA practices/implementation rate was low among colleges in the region. The study also revealed a lack of participatory governance and the existence of a poor communication system between staff and heads. The study contended that there is a need for heads (principals) of NMTCs in the Upper West region in Ghana should ensure the formation and functioning of QA units in their various institutions. These units should be empowered and allowed by heads to function as per recommendations by the regulatory bodies to support and to ensure quality training of nurses and midwives.